(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article discusses the most common vitamin deficiencies in calves and their impact on health. Vitamins play a crucial role in maintaining calf health. Deficiencies in vitamins A, D, E, and K can cause growth and development problems in calves. The article also includes helpful tips on what to do to prevent these vitamin deficiencies.